Genesis of indigenous Chakma Buddhists and their pulverization worldwide - Talukdar, S. P. (Delhi : Kalpaz, 2010)
Study on Chakma, Asian people of India.
Includes index and bibliographical references .
Keywords: Chakma (Asian people) -- History